KARAKTERISASI SIFAT MEKANIK BAHAN KOMPOSIT RAMAH LINGKUNGAN HASIL SINTESIS DARI SERAT LIDAH MERTUA (SANSEVIERA TRIFASCIATA) DAN SELULOSA BAKTERI - Putri Agustina Rohmawati; Yushardi Yushardi; Agus Abdul Gani (FKIP Universitas Jember, 2017)
The research has been done to know the characteristic of biodegradablecomposite material with leaf fiber Sanseviera trifascviata and bacterial cellulosematrix which has good mechanical properties so it is expected to be used as analternative to industrial raw materials. To achieve this goal the first step in thisresearch was making specimen with variation of fiber direction longitudinal andrandom. Then to know the characteristics of the material is done tensile .To determinethe biodegradability of the ingredients, the material was tested by the method of burialin the soil already available in the pot. From the research results obtained conclusionthe direction of fiber effect on the value of material strength, and modulus of materialelasticity. Material with the direction of longitudinal fiber has a value of tensilestrength and elastic modulus of 7.91 ± 1.46 and 3.70 ± 3.35 MPa, whereas in thedirection of random fiber that is 2.64 ± 0.26 and 0.90 ± 0, 86 MPa. In addition, thecomposite material that has been produced in this study is an environmentally friendlycomposite material due to biodegradable naturally.Keywords: Composites, Biodegradable, Sanseviera Trifasciata, Bakterial cellulose